Open Source Web GIS Solutions in Disaster Management – with Special Emphasis on Inland Excess Water Modeling - Juhász, Levente; Podolcsák, Ádámq; Doleschall, János (Journal of Environmental Geography, 2016)
In recent years, the increased frequency of inland excess water in the Carpathian Basin gets more and more attention. The authors developed a web based pilot application for disaster management, with special emphasis on inland excess water hazard management. Free and open source software was used to generate a model, and our work was based on Web GIS standards (OGC), which makes further development possible. The developed Web GIS application provides functions to support the data collection regarding channels and ditches, and on-line hydrological analysis based on OGC Web Processing Services (WPS). Hydrological analysis aims to visualize the areas potentially at risk, depending on different precipitation quantities and various values of influencing factors. In order to run the prototype a sample data set was gathered including reference maps, technical parameters and current condition of canals and ditches. The methodology of crowdsourcing can produce valuable Volunteered Geographic Information (VGI) that can fulfill the data requirements of disaster management applications. The prototype supports Crowdsourcing in the following aspects: free user access to the system’s analysis functionality, stakeholders may digitize the position of ditches, modify the status of the existing ditch system according to current conditions and add or modify parameters relevant for the analysis. The application demonstrated the usability of stakeholder generated geographic information and web processing for disaster management. The idea of integrating user-generated data into the various tasks of a disaster management agency is promising. However, maintaining data quality and standards compliance remain important issues.